Adherence to Physical Activity Among Diabetic Patients: A Study in Mbeya Region, Tanzania - Donath Damian; Philemon Laiza (Lifestyle Medicine)
ABSTRACT Background Adherence to physical activity (PA) recommendations among type 2 diabetes mellitus (T2DM) patients remains a global challenge, with significant implications for glycemic control and overall health outcomes. Despite the importance of PA, data regarding adherence rates and associated factors are limited, particularly in the Southern Highland zone of Tanzania. Methodology A cross‐sectional study was conducted at Mbeya Zonal Referral Hospital in Tanzania, targeting T2DM patients attending medical clinics between November and December 2022. Systematic sampling was employed, with 229 diabetic patients included in the study. Structured questionnaires were utilized for data collection, and statistical analysis was performed using Statistical Package for Social Sciences (SPSS) version 21. Results Among the 229 participants, 69% did not adhere to PA recommendations. The primary reasons for poor adherence included lack of skills (85.4%), willpower (76.6%), energy (69%), resources (65.2%), fear of injury (62.7%), social influence (57%), and time constraints (48.7%). Significant associations were found between physical inactivity and older age (67–83 years), female sex, and urban residence. Conclusion The study highlights the widespread non‐adherence to PA recommendations among T2DM patients in the Southern Highland zone of Tanzania. Barriers to adherence include personal factors, resource limitations, and social influences. Addressing these barriers through targeted interventions, such as skill‐building programs, awareness campaigns, and improved resource access, is essential to promote PA and improve glycemic control among T2DM patients. Further research is warranted to comprehensively understand the underlying causes of physical inactivity and develop effective strategies for promoting lifestyle modifications in this population.